Globalizáció és a nagyvárosi tér társadalmi szerkezete - Szirmai, Viktória (Szociológiai Szemle, 2024)
This study examines how the social structure of the European and Hungarian Metropolitan areas changes. Our analysis demonstrates the relationship between the new trends of urbanization, the spreading of the global economy and the reorganized society of the Metropolitans. Based on the main stream of the international and national researches and statistical analyses, an overview is presented on the areal effects of the global economic and historical trends, the differences between the areal social structures due to different economical development of the urban centers and their surrounding area, the social inequalities between the urban centers and their surrounding area.